TRIB3 promoter 33 bp VNTR is associated with the risk of cerebrovascular disease in type 2 diabetic patients - Lai, Jiaqi; Ouyang, Jiaying; Lin, Weijie; Liu, Mouze; Yang, Yang; Wang, Ruiqi; Yang, Haikui; Meng, Qian; Dong, Jiamei; Zhang, Jianping; Li, Ling; He, Fazhong (Frontiers in Genetics, 2022)
Previous studies have demonstrated that TRIB3 is closely related to insulin resistance, metabolic disorders and vascular diseases. Recently, it was reported that a 33 bp variable number of tandem repeats(VNTR) located in the TRIB3 promoter could considerably alter its transcriptional activity. Nonetheless, whether the shift of TRIB3 transcriptional activity has the effect of inducing diabetic vascular complications is still unclear. Therefore, in our study, we aimed to explore the relationship between the TRIB3 33bp VNTR and diabetic vascular complications. The TRIB3 33bp VNTR polymorphisms were determined by PCR and Sanger sequencing, a total of 798 eligible Chinese patients with type 2 diabetes(T2DM) were included in our study and then evaluated with clinical data. After adjusting for age, gender, BMI, smoking history, drinking history and duration of diabetes, we found that the high number of 33bp tandem repeats(repeats>8) was significantly associated with an increase in the risk of cerebrovascular diseases compared with the low number of 33bp tandem repeats(repeats≤6) in patients with T2DM(OR 2.66, 95% CI 1.29-5.47, p=0.008). The intermediate number of 33bp tandem repeats(6